Age-related changes in four-dimensional CMR-derived atrioventricular junction velocities and displacements: Implications for the identification of altered annular dynamics for ventricular function assessment. (March 2019) - Leng, Shuang; Zhao, Xiaodan; Koh, Angela S.; Zhao, Lei; Allen, John C.; Tan, Ru-San; Ma, Xiaohai; Zhong, Liang
Abstract: Background: We determined the age-related changes in atrioventricular junction (AVJ) velocities and displacements by feature tracking cardiovascular magnetic resonance (FT-CMR) in a healthy community-based population. We also investigated the importance of age-matching for the identification of altered AVJ dynamics. Methods: FT-CMR was performed in 230 controls (18–78 years) and in two patient groups each consisting of 40 subjects (group 1: 23–55 years, group 2: 56–80 years). AVJ dynamic parameters, including systolic velocity Sm, early diastolic velocity Em, late diastolic velocity Am, maximal systolic excursion MAPSE and the new parameter sweep surface area velocity SSAV were measured. Results: Increasing age in the control group was significantly associated with reductions in Sm, Em, MAPSE ( r = −0.40, −0.76, −0.34, all P < 0.001) and an increase in Am ( r = 0.45, P < 0.001). For patient group 1, the selection of an age-unmatched control group (56–76 years) underestimated the number of patients with abnormal AVJ dynamics during systole and early diastole (38% vs. 70% for Sm; 20% vs. 60% for Em; 35% vs. 50% for MAPSE). In contrast, for patient group 2, the number of patients with systolic and early diastolic AVJ dynamic abnormalities was overestimated (88% vs. 63% for Sm; 90% vs. 68% for Em; 73% vs. 58% for MAPSE) when compared with age-unmatched controls (24–55 years). Fifty-percent (20/40) of the sub-group of patients with normal left ventricular ejection fraction exhibited abnormal systolic Sm or MAPSE measurements. Conclusions: Significant correlations exist between age and AVJ dynamics. Age matching is important for evaluating AVJ long-axis function. Highlights: 4D atrioventricular junction (AVJ) dynamics by feature tracking CMR Provide age- and gender-specific normal ranges of AVJ dynamics AVJ dynamics significantly associated with age and gender Age matching is necessary for assessing severity of AVJ dynamic dysfunction.